Branched Platinum Nanostructures on Reduced Graphene: An excellent Transducer for Nonenzymatic Sensing of Hydrogen Peroxide and Biosensing of Xanthine. (10th July 2016) - Behera, Tapan Kumar; Sahu, Subash Chandra; Satpati, Biswarup; Bag, Bamaprasad; Sanjay, Kali; Jena, Bikash Kumar
Abstract: Here, a facile and highly sensitive platform has been developed for synthesizing branched Pt nanostructures on graphene. Graphene support has been employed to enhance the performance of platinum nanostructures (PtNs) in electrochemical sensing/biosensing. The graphene supported PtNs (GPtNs) modified electrode efficiently oxidises the H2 O2 at a lower potential in neutral phosphate buffer solution without employing the enzymes or redox mediators. The GPtNs electrode shows high sensitivity and can detect very low nanomolar concentrations (1 nM) of H2 O2 . It can linearly sense H2 O2 from 0-0.32 mM, and the sensitivity of the sensor was estimated to be 811.26 μAmM −1  cm −2 . The sensor shows excellent reproducibility, long time storage and operational stability. The sensor successfully estimates the H2 O2 concentration in the real sample (rainwater) for practical analysis. The interesting response of the sensor towards H2 O2 employed for fabrication of amperometric oxidase based biosensor for sensing of xanthine. The biosensor is highly stable and showed fast response in biocatalytic sensing of xanthine.